Depresión y su repercusión en el área emocional de una paciente de 17 años en el cantón Montalvo - Chang Izquierdo, Haydeé Katiuska (2022)
The present case study deals with the subject of depression and its repercussion in the emotional area of a 17-year-old adolescent from the Montalvo canton, where the necessary data for its elaboration were obtained, through interviews and a psychological test such as Beck's inventory test. Based on the results obtained, it was possible to detect that the patient has a presumptive diagnosis, which corresponds to major depressive disorder according to DSM-5, coded as follows: 296.23 (F32.2). The purpose of this case study is to detect how depression affects the emotional area, due to the separation from his partner he began to present low self-esteem, insecurity due to the emotional dependence he had with him, and even this situation that was going through led the patient to see a psychiatrist for the symptoms presented. For this reason, a psychotherapeutic scheme was implemented, based on cognitive behavioral therapy, in order to restructure the negative thoughts that he had towards himself and his environment, therefore, this will allow it to improve his emotional state and thus reintegrate. to the activities with his family and friends that he carried out normally.